Criminal Law Enforcement of Music Copyright in Indonesian Public Spaces: Proportionality and Ultimum Remedium in Balancing Copyright Protection and Cultural Access - Rr. Dijan Widijowati; Restu Adhie Charisma (Khazanah Hukum, 2026)
The use of music in public spaces is a common social practice, yet it often gives rise to tension between music copyright protection and public access to culture. Conventional enforcement measures, including sweeping activities directed at the use of music in public spaces, may adversely affect public appreciation of music and risk constraining the development of local musical expression. This study examines the legal dynamics of that tension through a normative juridical approach, with a focus on the use of music in Indonesian public spaces. The data were collected through a literature-based analysis of copyright legislation, legal doctrine, and practices of criminal law enforcement. The findings show that copyright protection remains essential to safeguard the economic and moral rights of creators and to sustain creative production. However, its enforcement must also take into account the principles of proportionality, tolerance, and the broader public interest in cultural access. This article argues that criminal law enforcement against music copyright infringement should be applied only when the elements of mens rea and actus reus are clearly established, and when alternative dispute resolution mechanisms or other legal remedies are insufficient to protect the rights of copyright holders. The study concludes that criminal sanctions should be limited to intentional and legally significant infringements, while ordinary licensing disputes should primarily be addressed through civil, administrative, or other non-penal mechanisms. This study contributes to Indonesian copyright scholarship by conceptualizing criminal liability for public music use through the doctrinal framework of mens rea, actus reus, proportionality, and ultimum remedium.